El Excentrico, 1971-04-05 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
April 5, 1971 [5 de abril de 1971]. No volume or issue number. Cover has a photograph of Al Garza for the City Council Seat No. 3 election